Analysis of Sharia Partnership Program Implementation, Sustainability Management, and Green Technology Use on Sustainable Economic Development in Banten - Azis, Slamet Abdul; Suhara, Ade; Suhendra, Agus; Mayasari, Nanny; Yuliastuti, Hilda (West Science Social and Humanities Studies, 2024)
This study examines the impact of the Sharia Partnership Programme, sustainability management, and green technology use on sustainable economic development in Banten. Employing a quantitative approach, data were collected from 170 respondents using a Likert scale and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The results indicate that all three factors have significant positive effects on sustainable economic development, highlighting the importance of integrating ethical financial practices, sustainability management, and technological innovations. The findings suggest that these strategies play a crucial role in promoting sustainable growth, offering valuable insights for policymakers and business leaders seeking to enhance sustainability efforts in Banten and similar regions. This study contributes to the theoretical understanding of sustainable development and provides practical recommendations for fostering economic growth that aligns with social and environmental goals.